2018
DOI: 10.3389/fpsyg.2018.00654
|View full text |Cite
|
Sign up to set email alerts
|

‘Killing Me Softly With His/Her Song’: How Leaders Dismantle Followers’ Sense of Work Meaningfulness

Abstract: Leaders influence followers’ meaning and play a key role in shaping their employees’ experience of work meaningfulness. While the dominant perspective in theory and in empirical work focuses on the positive influence of leaders on followers’ work meaningfulness, our conceptual model explores conditions in which leaders may harm followers’ sense of meaning. We introduce six types of conditions: leaders’ personality traits, leaders’ behaviors, the relationship between leader and follower, followers’ attributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 111 publications
1
12
0
Order By: Relevance
“…The studies' results have implications for organizations and employees alike. Based on research to date, organizations aiming to enhance their employees' experience of work meaningfulness could do so by increasing task significance, that is, by increasing employees' positive impact on others or by making them more aware of this impact (e.g., Allan et al, 2018; Grant, 2008), or through leadership (e.g., Arnold et al, 2007; Carton, 2017; Kipfelsberger & Kark, 2018). Our findings highlight creating beneficial conditions for proactive work behavior as an additional avenue to foster work meaningfulness.…”
Section: Discussionmentioning
confidence: 99%
“…The studies' results have implications for organizations and employees alike. Based on research to date, organizations aiming to enhance their employees' experience of work meaningfulness could do so by increasing task significance, that is, by increasing employees' positive impact on others or by making them more aware of this impact (e.g., Allan et al, 2018; Grant, 2008), or through leadership (e.g., Arnold et al, 2007; Carton, 2017; Kipfelsberger & Kark, 2018). Our findings highlight creating beneficial conditions for proactive work behavior as an additional avenue to foster work meaningfulness.…”
Section: Discussionmentioning
confidence: 99%
“…To be more specific, differences between leader thoughts of follower attributions and actual follower attributions can affect team morale (Coetzee & Henning, 2019). Followers’ sense of work meaningfulness might be reduced by some variables such as the relationships between leaders and followers, leaders' traits and behaviors, and followers' characteristics (Kipfelsberger & Kark, 2018). Followers' mindfulness can influence the matching levels of strategic optimism and work engagement between leaders and followers (Bunjak & Černe, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that individuals tend to find their work meaningful when they work in an organizational climate of openness and collaboration climate and also when they can perform tasks of significance and discretion (for reviews, see Lysova et al, 2019;Rosso et al, 2010). Relatively scant attention has been paid to how and when leaders could develop their employees' work meaningfulness (e.g., Chaudhary, 2020;Kipfelsberger & Kark, 2018). This insufficiency is unfortunate because leaders, standing as a proximal context where employees are embedded (Salancik & Pfeffer, 1978), should play an important role in crafting their employees' work meaningfulness.…”
Section: Palabras Clavementioning
confidence: 99%